Proceedings of the 2017 ACM International Conference on Interactive Surfaces and Spaces 2017
DOI: 10.1145/3132272.3134132
|View full text |Cite
|
Sign up to set email alerts
|

Programmable Liquid Matter

Abstract: Figure 1. Programmable liquid matter making nonlinear shape of alphabet "S". 7x7 electrodes array dynamic switching to control EGaIn to make an 'S' shape. ABSTRACTIn this paper, we demonstrate a method for the dynamic 2D transformation of liquid matter and present unique organic animations based on spatio-temporally controlled electric fields.In particular, we deploy a droplet of liquid metal (Gallium indium eutectic alloy) in a 7x7 electrode array prototype system, featuring an integrated image tracking syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Based on this principle, a typical early exploration showed that a continuous pattern could be Need electrolytes [60,102,193,194] formed by changing the polarity of the electrodes. [88] Multiple electrodes were used because elongated liquid metal exhibits fluid instability. Aiming to overcome this challenge, Li et al [89] proposed that a liquid metal doped with Fe could suppress instabilities owing to the decrease in surface tension from electrochemical oxidation, thereby allowing the liquid metal to be stretched to tens of times its original length.…”
Section: Response Properties Of Liquid Metal Smart Materialsmentioning
confidence: 99%
“…Based on this principle, a typical early exploration showed that a continuous pattern could be Need electrolytes [60,102,193,194] formed by changing the polarity of the electrodes. [88] Multiple electrodes were used because elongated liquid metal exhibits fluid instability. Aiming to overcome this challenge, Li et al [89] proposed that a liquid metal doped with Fe could suppress instabilities owing to the decrease in surface tension from electrochemical oxidation, thereby allowing the liquid metal to be stretched to tens of times its original length.…”
Section: Response Properties Of Liquid Metal Smart Materialsmentioning
confidence: 99%
“…Unique properties of liquid materials have been exploited in fluidic devices to create diverse applications such as sensing input [42, 49-51, 54, 58], visual and haptic output [15,18,27,48,55], and soft robotics [2,11,22,30,53,57]. Recent advances in the use of fluidics in human-computer interaction explore the interactive capabilities of fluidic mechanisms [34] and shape-changing materials [28].…”
Section: Fluidic Devicesmentioning
confidence: 99%
“…Based on these merits, a wide range of applications can be developed, such as microelectromechanical systems (MEMS) switches and conductive microcomponents [62]. Tokuda et al demonstrated novel manipulation of liquid metal with a vision to expand the work on shape changing, programmable material and consider its use as a method for providing a programmable electric circuit [63]. Figure 16 shows work mechanism for liquid metal deformation, and the liquid metal can deform in a desired shape by adjusting the voltages among the electrode array.…”
Section: Transformationmentioning
confidence: 99%
“…Figure 16 shows work mechanism for liquid metal deformation, and the liquid metal can deform in a desired shape by adjusting the voltages among the electrode array. These techniques provide a new platform to realise novel manipulation and detailed 2D control of liquid metals under a programmable electric circuit [63].…”
Section: Transformationmentioning
confidence: 99%